Green-chemistry Compatible Approach to TiO2-supported PdAu Bimetallic Nanoparticles for Solvent-free 1-Phenylethanol Oxidation under Mild Conditions - Chang, Jian-Bing; Liu, Chang-Hai; Liu, Jie; Zhou, Yu-Yan; Gao, Xu; Wang, Sui-Dong (Nano-Micro Letters, 2015)
TiO2-supported PdAu bimetallic nanoparticles (NPs) with small size and good dispersity were prepared by the room-temperature ionic liquid-assisted bimetal sputtering, which is simple, environmentally friendly, and free of additives and byproducts. Pd/Au atomic ratio can be tuned by controlling the sputtering conditions simply. High catalytic activity was found in PdAu–NPs–TiO2 hybrids for solvent-free selective oxidation of 1-phenylethanol using O2 as the oxidant at the low temperature of 50 °C and low pressure of 1 atm. It was found that Pd/Au ratio strongly affected the catalytical activity, and the highest conversion of about 35 % and turnover frequency of about 421 h−1 were achieved at 1:1 of Pd/Au atomic ratio. The synergistic effect in PdAu NPs was also discussed based on the comprehensive characterization results. The present approach may offer an alternative platform for future development of green-chemistry compatible bimetallic nanocatalysts.